Harmonization Gap in Financial Reporting - A Descriptive Analysis - Goel, Sandeep (Indian Journal of Finance, 2011)
Financial reporting includes not only financial statements, but also other means of communicating information that relates, directly or indirectly, to the information provided by the accounting system. Corporate annual reports (CAR) are the subject of research emanating from different disciplines. Full and fair disclosure through these annual reports is always a welcome note for better results. Equally inevitable is ’the harmonization of reporting practices of the countries.’ Globalization, undoubtedly, is the key requirement for determining the future of financial reporting. The present discussion becomes altogether more relevant when countries are seriously considering adopting international accounting standards and India is positioned to be a strong leader. India has already started gearing up for the implementation of IFRS. The present article analyzes the global financial reporting scenario descriptively and stresses upon the need for harmonization of international financial reporting.